Contribuições da organização do conhecimento e da Arquivologia para a definição de pontos de acesso aos documentos da Comissão da Verdade da Universidade Federal do Rio Grande do Norte - Jacyara Kalina Themistocles da Silva (2023)
Documents are fundamental sources of information that contribute to the preservation of democratic societies. In this regard, the archival collections of Truth Commissions hold historical and social value as they are memorial records that provide evidence of the violations committed during the military dictatorship. Within this context, this research presents the work carried out by the Truth Commission of the Federal University of Rio Grande do Norte (CV-UFRN), highlighting its contribution to the preservation and access to documents that reveal human rights violations during the military dictatorship. However, despite the importance of these documents, their retrieval in an easy, organized, and accessible manner within the current digital database lacks improvement. One of the main difficulties encountered is the lack of metadata, which are regarded in Archival Science as access points capable of aiding document retrieval. Consequently, reflection is necessary on the need for studies in the fields of Archival Science and Knowledge Organization to contribute to the recovery and access of CV-UFRN documents through the establishment of access points. Thus, the guiding question of this study is: How can Knowledge Organization and Archival Science instruments/methodologies contribute to the treatment and access to the documents produced and collected during the work of CV-UFRN? This research problem emerged based on the following assumptions: (1) Knowledge Organization provides inputs that can contribute to the retrieval of CV-UFRN documents, (2) document representation can also occur based on their contextualization and content, as advocated by Archival Science studies, and (3) through multi-level archival description, which starts from the general to the specific and from relevant information to the level of description, it will be possible to contribute to the access of CV-UFRN documents, following the guidelines of the Brazilian Norm for Archival Description (NOBRADE). Therefore, this research seeks to investigate the instruments/methodologies of Knowledge Organization and Archival Science for the treatment and definition of access points to the documents produced and collected during the work of CV-UFRN. To achieve this goal, a bibliographic, documentary, exploratory research of an applied nature, and qualitative approach were conducted. The following methodological procedures were carried out: Firstly, a bibliographic research was conducted. Then, requests for information were made to UFRN, the General Archive, and the Image Laboratory of the mentioned university. Subsequently, descriptive elements were identified based on NOBRADE, and the selection of a terminological control instrument was performed. Additionally, contributions from Knowledge Organization studies presented in the Working Group 2 - Organization and Representation of Knowledge at the National Meeting of Research in Information Science were sought. Thus, contributions from Knowledge Organization were identified, highlighting documentary analysis, indexing, and the utilization of a thesaurus. Finally, these contributions enabled the application of interdisciplinary approaches between Knowledge Organization and Archival Science, resulting in the proposed definition of access points to the aforementioned documents.